PERGUMULAN ISLAM DAN KOLONIALISME ABAD KE 18 DAN 19 - Daulay, Syaripuddin (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2021)
Since the 16th century the colonizers came to Indonesia one after another. Starting with the Portuguese, then moving on to the Netherlands and ending with the Japanese. After that, actually there was colonialism carried out by the British before Indonesia's independence. Although briefly, but enough to swallow many victims and various losses. Indeed, until the end of the 19th century colonialism was still visible in various parts of the world. This paper is qualitative, with a library research approach. The struggle of Muslims with colonialism in the field of education was when the Dutch discriminated against Islamic educational institutions (pesantren). In the field of the Dutch economy managed to make the Muslim economy slumped. At first the Muslim profession was located in the center of trade but was taken over by the Dutch by spreading false Hadith that